Učenci, žrtve medvrstniškega nasilja - Cvak, Mihaela; Pšunder, Majda (Revija za elementarno izobraževanje, 2013)
Pupils as Victims of Peer Violence. The school is an educational institution that has to provide appropriate control of adults over pupils, which they do. Nevertheless, violence cannot be avoided. Pupils encounter peer violence in different roles, as observers, victims, perpetrators, or both. The objective of our research was to examine how often pupils are victims of peer violence, and to what extent the latter depends on pupils’ gender and age. The results of the research made among pupils in the fifth, seventh, and eighth grades of various primary schools across Slovenia showed that 24.1 per cent of pupils had already been victims of peer violence. The ones that they tend to tell about such episodes are their parents. The results have also shown that school is really a place where violence is very common, and that psychological and verbal abuse are the most common types of violence used.